The cumulative effect of chronic stress and depressive symptoms affects heart rate in a working population - Lutin, Erika; Schiweck, Carmen; Cornelis, Jan; De Raedt, Walter; Reif, Andreas; Vrieze, Elske; Claes, Stephan; Van Hoof, Chris (Frontiers in Psychiatry, 2022)
Background: Chronic stress and depressive symptoms have both been linked to increased heart rate (HR) and reduced heart rate variability. However, up to date, it is not clear whether chronic stress, the mechanisms intrinsic to depression or a combination of both cause these alterations. Subclinical cases may help to answer these questions. In a healthy working population, we aimed to investigate whether the effect of chronic stress on HR circadian rhythm depends on the presence of depressive symptoms and whether chronic stress and depressive symptoms have differential effects on HR reactivity to an acute stressor. Methods: 1002 individuals of the SWEET study completed baseline questionnaires, including psychological information, and five days of electrocardiogram (ECG) measurements. Complete datasets were available for 516 individuals. In addition, a subset (n=194) of these participants completed the MIST stress task on a mobile device. Participants were grouped according to their scores for the Depression Anxiety Stress Scale (DASS) and Perceived Stress Scale (PSS). We explored the resulting groups for differences in HR circadian rhythm and stress reactivity using linear mixed effect models. Results: High and extreme stress alone did not alter HR circadian rhythm, apart from a limited increase in basal HR. Yet, if depressive symptoms were present, extreme chronic stress levels did lead to aberrant circadian rhythm. Furthermore, blunted stress reactivity was associated with depressive symptoms, but not chronic stress. Conclusion: Clinicians should be aware that the combination of stress and depressive symptoms could be a warning sign for worse cardiovascular health.